Tinea Corporis pada Pasien Obese Grade II: Laporan Kasus - Sifa’ Syaharani Fairuz Hanan; Tutik Ernawati (Medula, 2026)
Tinea Corporis is a superficial fungal infection caused by dermatophytes affecting the skin, excluding the palms, soles, and groin. Tinea Corporis is a recurrent and potentially spreading disease; therefore, it requires a holistic management approach. Family physicians play an important role in providing comprehensive care by identifying risk factors, clinical problems, and implementing evidence-based management through a patient-centered, family-oriented, and community-oriented approach. This study is a case report. Primary data were obtained through history taking, physical examination, and home visits, while secondary data were collected from the patient’s medical records. Assessment was based on a holistic diagnosis at the beginning, during the process, and at the end of the study using qualitative and quantitative evaluations. A 42-year-old woman presented with erythematous patches accompanied by itching beneath both breasts for six days. Family members had experienced similar complaints. Based on the history and physical examination, the patient was diagnosed with Tinea Corporis. The patient also had grade II obesity, which is a risk factor for dermatophyte infection due to increased skin folds, moisture, and friction that may promote fungal growth and increase the risk of recurrence. Non-pharmacological and pharmacological interventions, including patient and family education regarding the disease, were provided through three home visits. The outcome of this case demonstrated clinical improvement, as indicated by the reduction of symptoms and positive behavioral changes. Family support and involvement remained essential components in the treatment and recovery process.